The Effect of Progressive Muscle Relaxation (PMR) on The Mother's Anxiety Level Before Sectio Caesarea at Dinda’s Hospital at Tangerang City - Lastri Mei Winarni; Siti Nurjannah; Yati Afiyanti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: The process of delivery through sectio caesarea is a complex event and causes anxiety. Anxiety that occurs can have a negative impact on mothers and babies born. This study aims to determine the effect of progressive muscle relaxation (PMR) on the level of anxiety of mothers  before sectio caesarea at Dinda’s Hospital, Tangerang City.Methods: The research method uses a quantitative approach with a quasi-experimental non-equivalent control group conducted on 36 respondents with a simple random sampling technique. Intrument of this study used Zung Self-Report Anxiety Scale (ZSAS) to measure mothers anxiety levels. Intervention delivered to the respondent by researcher a day before enter the operating room. Data processing using editing, coding, cleaning and analysis, to test the effect of PMR to mothers anxiety level, data analysis used independent paired T-test.Results: Result of the analysis show that the provision of PMR  techniques can reduce score anxiety levels by 8.2, from 58.3 before  intervention to 50.1. The results show that independent paired  t-test obtained p-value of 0.001 which means that there is a significant effect between the level of anxiety of the mothers before SC surgery compare with control group.Conclusions: Nurses need to implement and educated mothers about PMR intervention to help  reduce the level of anxiety before sectio Caesarea.